Orthogonally engineering matrix topography and rigidity to regulate multicellular morphology - Hu, Benhui (2014)
Programmable polymer substrates, which mimic the variable extracellular matrices in living systems, are used to regulate multicellular morphology, via orthogonally modulating the matrix topography and elasticity. The multicellular morphology is dependent on the competition between cell–matrix adhesion and cell–cell adhesion. Decreasing the cell–matrix adhesion provokes cytoskeleton reorganization, inhibits lamellipodial crawling, and thus enhances the leakiness of multicellular morphology.